(untitled) (The Review of Diabetic Studies, 2024)
Background Cancer is emerging as a major global health-care system challenge with a growing burden worldwide. Due to the inconsistent cancer registry system in Saudi Arabia, the epidemiology of cancer is still dispersed in the country. Consequently, cancer (BC) has a major impact on health of women worldwide and the Kingdom of Saudi Arabia (KSA) is no exception. It is considered the most common malignancy and embodies the second leading cause of cancer deaths after lung cancer. The malignancy carries tremendous socio-economic, emotional, and public health implications. Disease and treatment confound abilities to successfully achieve age-related developmental tasks, such as establishing autonomy and making independent decisions about employment, education, relationships, and starting a family. All of these stressors may interfere with adherence to therapy and ultimately impact emotional and social maturation. Emerging evidence suggests that the biomedical risks and psychosocial issues for are distinct from those of both patients and older adult populations and those patients with cancer may be served inadequately or inappropriately by existing cancer services. For example, disparities in survival outcomes for patients with cancer have been observed, favouring patients who are treated on protocols as opposed for the same disease. Aim of the study: To review the epidemiology of cancer in Saudi Arabia and pattern of cancer in the Kingdom of Saudi Arabia 2024. Method: This systematic review utilized the PubMed database for data extraction, including freely accessible studies published in the last 5 years. 7 articles from different study designs were included, while awareness and non-English language studies were excluded. Results: In recent years, the concept of epidemiology of cancer in Saudi Arabia a systematic review 2024. With regard to age-standardized rates (ASR), the incidence of all cancers excluding non-melanoma skin cancer was estimated to be 17,522 cases (8,296 males and 9,226 females) in Saudi Arabia. Conclusion: The overall incidence of cancer in Saudi Arabia has been rising. To lower the incidence and mortality of cancer in Saudi Arabia, primary, secondary, and tertiary prevention are all very important. The most crucial aspect is to concentrate on primary prevention, which may involve raising public awareness of cancer risk factors and strategies for reducing or eliminating them and health-related concerns about the future are particularly distressing.